Effect of welding parameters on the mechanical and microstructural properties of friction stir welded AA- 2014 joints. (August 2016) - Khan, R.; Bhatty, M. B.; Iqbal, F.; Zaigham, H.; Salam, I.
Abstract: In this study, the effect of processing parameters on the mechanical and microstructural properties of aluminum AA2014-T6 joints produced by friction stir welding was analyzed. Friction stir welding was carried out on a milling machine. Different samples were produced by varying the tool rotational rates (700, 1000 rpm) and travel speeds (45-105 mm/min). Tensile tests performed at room temperature were used to evaluate the mechanical properties of the joints. In order to analyze the microstructural evolution of the material, the welds' cross-sections were observed under optical microscope. The results shows that the resulting microstructure is free of defects and tensile strength of the welded joints is upto 75% of the base metal strength.